12 adventurers with disabilities - Perry, Susan, 1950- (No barriers (12 Story Library (Firm)), 2020)
Profiles twelve people with disabilities who nevertheless became athletes and world adventurers--such as blind rock climber Erik Weihenmayer and armless pilot Jessica Cox. Includes a glossary.